Immigration, unemployment and growth in the host country: Bootstrap panel Granger causality analysis on OECD countries - Ekrame Boubtane; Dramane Coulibaly; Christophe Rault (Institute for the Study of Labor (IZA), 2011)
This paper examines the causality relationship between immigration, unemployment and economic growth of the host country. We employ the bootstrap panel Granger causality testing approach of Kónya (2006) that allows to test for causality on each individual country separably by accounting for dependence across countries. Using annual data over the period 1980-2005 for 22 OECD countries, we find that, only in Portugal, unemployment negatively causes immigration, while in any country, immigration does not cause unemployment. We also find that, in France, Iceland, Norway and United Kingdom, growth positively causes immigration, while in any country, immigration does not cause growth.
urn:nbn:de:101:1-201107283796
Keywords: E20; F22; J61; 330; immigration; growth; unemployment; Granger causality